Risk Factors for the Occurrence of Surgical Wound Infection in Post-Caesarean Section Patients - Rahma Fauziyah; Titiek Idayanti; Widya Anggraeni (Jurnal Midpro, 2026)
Surgical wound infection (SWI) is one of the most common complications that occur after surgical procedures, including in post-Caesarean section (CS) patients. Many factors can influence the occurrence of surgical wound infections, including age, obstetric history, nutritional status, obesity, comorbidities, immune system, and hemoglobin levels. The purpose of this study is to identify the risk factors associated with the incidence of surgical wound infections in post-Caesarean section patients. The research design used is analytic with a cross-sectional approach. The population in this study includes all post-Caesarean section patients at RS Dian Husada Mojokerto. The sampling technique used is accidental sampling. The sample consists of all post-Caesarean section mothers who experienced post-Caesarean section wound infections and meet the criteria. The independent variable in this study is the risk factors for post-Caesarean section wound infections. The dependent variable in this study is post-Caesarean section wound infections. Data analysis was conducted using the Chi-Square statistical test. The research results show that all risk factors causing post-C-section wound infection have a significant relationship. Factors such as age, Hb levels, nutritional status, obesity, delivery history, immunity, and comorbidities all pose a risk of causing post-C-section wound infection. It is expected that healthcare workers or hospital authorities improve the standard operating procedures (SOP) related to the prevention of surgical wounds, especially in post-C-section patients. Patients are also expected to pay attention to the cleanliness of post-C-section wounds and follow the advice of healthcare professionals.